Influence of the Pt size and CeO2 morphology at the Pt–CeO2 interface in CO oxidation. Issue 46 (22nd November 2021) - Yoon, Sinmyung; Ha, Hyunwoo; Kim, Jihun; Nam, Eonu; Yoo, Mi; Jeong, Beomgyun; Kim, Hyun You; An, Kwangjin
Abstract : The catalytic activity derived from the metal–support interaction at the Pt–CeO2 interface can be demonstrated by the two descriptors of Pt particle size and CeO2 morphology. Abstract : Understanding the inherent catalytic nature of the interface between metal nanoparticles (NPs) and oxide supports enables the rational design of metal–support interactions for high catalytic performance. Electronic interactions at the metal–oxide interface create active interfacial sites that produce distinctive catalytic functions. However, because the overall catalytic properties of the interface are influenced by several complex structural factors, it is difficult to express the catalytic activity induced by the interfacial site through a simple descriptor. Based on a combinatorial study of density functional theory calculations and catalytic experiments, we focus on two structural design factors of metal NP-supported oxide catalysts: the size of Pt NPs and the morphology of the CeO2 support. Pt NPs with sizes of 1, 2, and 3 nm were supported on the surface of CeO2 -cubic (100 facet) and -octahedral (111 facet) nanocrystals. During catalytic CO oxidation, the activity of the Pt/CeO2 -cube was higher than that of the Pt/CeO2 -octahedron, regardless of the size of the NPs. Although 1 nm Pt NPs donate a similar number of electrons per Pt atom to CeO2 -cubes and CeO2 -octahedra, the inherently low oxygen vacancy formation energy of the CeO2 (100) surface leads to the higher catalytic activity of the Pt–CeO2 -cube interface. However, the intrinsic catalytic activity of the interface between Pt NPs and two CeO2 nanocrystals converges as the size of Pt NPs increases. Because large Pt NPs interact more strongly with CeO2 (100) than CeO2 (111), the positive effect of the low vacancy formation energy of CeO2 (100) is compensated by the strengthened Pt–O interaction. This study elucidates how the interfaces formed between the shape-controlled CeO2 and the size-controlled Pt NPs affect the resultant catalytic activity.